Learning strategies used by the students of Readings and Conversations I at the Foreign Languages Department of the University of El Salvador, semester II, 2013. - Guerra Quant, Alicia Yoselin; Herrera Gutiérrez, José Leonel; Garay Salinas, Ricardo; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Over the past two decades learner centered approaches have become increasingly studied while the grammar translation method and other approaches had gone out of fashion, Rahimi and Farvardin (2009). Thus, in order to lead students to develop an independent and autonomous language learning, it is necessary to point out the language learning strategies students are using at the Foreign Language Department to enhance the learning of the English language. Nevertheless, research in this area has shown that not all learners use learning strategies in the same fashion. Rebeca Oxford and Nyikos (1989), Oxford (1990) stated that there are many variables inferring in the type and frequency of the learning strategies used by second foreign language learners. This study is divided in six chapters preceded with an introduction which is a general view about this work. Thus, the first chapter is the statement of the problem which presents a brief description of the problem, the justification, the general and specific objectives and the key terms. The second chapter is the review of related and relevant literature linked directly with the aims of this work.
Incluye anexos.
Bibliográfia : hojas 45-46
Keywords: Inglés -- Enseñanza; Métodos de enseñanza; Adquisición de segundo lenguaje; Learning methods